Violent differences : the importance of race in sexual assault against queer men - Meyer, Doug, 1980- (University of California Press, 2022)
"Although sexual assault has received increasing attention since #MeToo became widely known, little attention has focused on the experiences of queer men who have experienced this violence. Violent Differences is the first book of its kind to focus specifically on queer male survivors and to devote particular attention to Black queer men. While previous scholarship on male survivors has emphasized the role of masculinity, Doug Meyer shows that race and sexuality should be considered as equally foundational as gender. Instead of considering sexual assault against queer men in the abstract, this book draws attention to survivors' lived experiences. Meyer examines interview data with 60 queer men who have experienced sexual assault, highlighting their interactions with the police and their experiences of victim blaming. This book expands approaches to sexual assault through an analysis of a new group of survivors and by revealing that race, gender, and sexuality all remain essential for understanding how this violence is experienced"--